PETROLOGY AND GEOCHEMISTRY OF PRIMITIVE LOWER OCEANIC CRUST FROM PITO DEEP: IMPLICATIONS FOR THE ACCRETION OF THE LOWER CRUST AT THE SOUTHERN EAST PACIFIC RISE - Perk N.W.; Coogan L.A.; Karson J.A.; Klein E.M.; Hanna H.D. (My University, 2007)
A suite of samples collected from the uppermost part of the plutonic section of the oceanic crust formed at the southern East Pacific Rise and exposed at the Pito Deep has been examined. These rocks were sampled in situ by ROV and lie beneath a complete upper crustal section providing geological context. This is only the second area (after the Hess Deep) in which a substantial depth into the plutonic complex formed at the East Pacific Rise has been sampled in situ and reveals significant spatial heterogeneity in the plutonic complex. In contrast to the uppermost plutonic rocks at Hess Deep, the rocks studied here are generally primitive with olivine forsterite contents mainly between 85 and 88 and including many troctolites. The melt that the majority of the samples crystallized from was aggregated normal mid-ocean ridge basalt (MORB). Despite this high Mg# clinopyroxene is common despite model predictions that clinopyroxene should not reach the liquidus early during low-pressure crystallization of MORB. Stochastic modeling of melt crystallisation at various levels in the crust suggests that it is unlikely that a significant melt mass crystallized in the deeper crust (for example in sills) because this would lead to more evolved shallow level plutonic rocks. Similar to the upper plutonic section at Hess Deep, and in the Oman ophiolite, many samples show a steeply dipping, axis-parallel, magmatic fabric. This suggests that vertical magmatic flow is an important process in the upper part of the seismic low velocity zone beneath fast-spreading ridges. We suggest that both temporal and spatial (along-axis) variability in the magmatic and hydrothermal systems can explain the differences observed between the Hess Deep and Pito Deep plutonics.
Keywords: PITO DEEP; EAST PACIFIC RISE; MAGMA CHAMBER; MID-OCEAN RIDGE